A study on predictors of severe dengue in pediatric patients in a tertiary care hospital in Telangana - Archana Reddy Dami Reddy; Sumanth Reddy Musali (Indian Journal of Child Health, 2021)
Background: Dengue is an emerging arthropod borne disease with increasing incidence in recent years in several countries, especially India. Early recognition of progression of disease helps in triage and timely management of fluids to decrease mortality. Objective: The objective of the study was to identify the predictive factors for severe dengue in pediatric patients for hospitalization for close monitoring. Methods: This was a prospective observational study conducted in the department of pediatrics in a tertiary care hospital in Mahbubnagar from June 2019 to May 2020. One hundred and four children between the age group of 0 and 15 years with probable dengue symptoms who were willing to get admitted were included in the study cohort. Thorough history and clinical examination, basic laboratory investigations such as complete blood picture, hematocrit, liver function tests, renal function tests (RFTs), serum electrolytes, serum ferritin, and coagulation profile were done as needed. All the patients were grouped into two groups – non-severe dengue (dengue fever without warning signs and dengue fever with warning signs) and severe dengue as per the World Health Organization guidelines. All the variables were analyzed using SPSS software. Results: Out of 104 confirmed cases, majority of the admissions were in 5–10 years age group (51.9%). Male children were 61.5%. Mean duration of hospitalization was 4.79±2.96 days. Fever (97.1%) was the most common symptom followed by anorexia (86.5%) and lethargy (82.7%). Symptoms such as lethargy, vomiting, abdominal pain/epigastric tenderness, epistaxis, edema, and altered sensorium were more commonly associated with severe dengue. Hepatomegaly (53.9%) was the most common clinical sign followed by epigastric tenderness (58.7%). Hepatomegaly, splenomegaly, ascites, gallbladder edema, pleural effusion, low pulse pressure, hypotension, oliguria, and significant gastrointestinal bleeds were more common in severe dengue group. Platelet count